(untitled) (Research, Society and Development, 2021)
Contamination of effluents often occurs due to improper disposal of textile dyes or their by-products. These can often be carcinogenic and/or mutagenic to the biome. Given the above, the need for effective methods for treating effluents is clear. This treatment occurs by biological, physical, and/or chemical processes. Regarding chemical processes, heterogeneous photocatalysis stands out, mainly because it guarantees an effective degradation of contaminants. In this sense, mixed metal oxides, act as photocatalysts and constitute structures capable of producing a large family of solids with physical properties suitable for the degradation of many pollutants. Modified ABO3 perovskites, as in the case of the SrZrxSn1-xO3 semiconductor system, are effective in the degradation of textile dyes in effluents. The present work aimed to use the Box-Behnken model to evaluate the performance of the oxides resulting from the structural modifications of the perovskite SrZrxSn1-xO3 system, concerning the discoloration of the golden yellow dye remazol. The synthesized oxides were characterized by instrumental techniques and a Box-Behnken 34 project was developed. From this, the influence of some factors such as structural modification, oxide mass, exposure time, and the number of UVC lamps was evaluated. The discoloration of the dye was monitored from the attenuation of the absorbance at the wavelength 411 nm. According to the results obtained, the highest percentage of discoloration was obtained using the modified oxide SrZr0,25Sn0,75O3 for an approximate time of 6 hours in contact with 1 UVC lamp.